(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This study introduces an innovative mathematical model developed to calculate albedo as a function of wave height and wind speed, two critical parameters that enhance the efficiency of photovoltaic panels used by unmanned surface vehicles (USVs) in dynamic hydrometeorological conditions. Albedo, defined as the proportion of energy reflected by a surface, significantly impacts the conversion of solar radiation into electrical power. The proposed model underwent validation through both simulations and experimental measurements using LabVIEW and DIAdem tools, demonstrating a 96% accuracy under real-world conditions. These results confirm the model’s effectiveness in forecasting energy output and optimizing energy management for autonomous maritime operations.